(untitled) (Raíces: Revista de Ciencias Sociales y Políticas, 2022)
This research was carried out in the Lomas Del Gavilán region, Nindirí-Masaya, with the purpose of characterizing agricultural activities and land use. The methodology used was descriptive, with a quantitative approach, the population was made up of 10 agricultural producers, integrating the sample of this research, the study variables are, agricultural activity, soil resource, impact of agricultural activities, good land use practices. For the collection of information, techniques were used, among them: the interview with state institutions present in the region, and later the application of the survey to the producers. The Lomas Del Gavilán region is a small area of 4.6 km2 (AMUSCLAM, 2011-2012), dedicated to agricultural activities including corn, beans, citrus fruits, vegetables. The existing activities in this region have generated a negative impact on the soil, due to overexploitation, bad agricultural practices, inappropriate use and deforestation that cause an accelerated process of soil erosion. Accelerated soil degradation processes are observed in the area, which can be manifested in the reduction of crops, especially in basic grains, and in the accumulation of sediments in the lower parts of the region.